Polytrichlorosilylstyrenes: Exploiting the β-Effect for Polymer Synthesis - Sebastian, Thomas (My University, 1990)
Trimethylsilylstyrenes undergo protiodesilylation (Scheme 1, path A), via the β-silyl carbonium ion under acidic conditions. In contrast, the corresponding trichlorosilyl substituted compound was found to undergo an oligomerization reaction (Scheme 1, path B) with triflic acid as the catalyst. (See Diagram in Thesis)
The β-effect [(σ-p)π overlap] may play a significant role in the weakening of the silicon-carbon bond and thus promote the cleavage process, as is observed in scheme 1, path A. Introduction of electronegative chloro groups on silicon weakens the β-effect and hence the silyl leaving group ability, resulting in oligomerization of the styrene (Scheme 1, path B).
In this oligomerization reaction, chain termination by an internal Friedel-Crafts reaction competes with the chain propagation. As a result, indane terminated low moldecular weight oligomers are formed. The case is similar to β-methyldichlorosilylstyrene, with the only difference that here ca. 20% desilylation has occured, again reflecting the fact that subtle changes in the β-effect acan influence the course of electrophilic reactions.
Keywords: polymer, synthesis, polytrichlororsilylstyrenes, silicon-carbon, bond, reactions, catalyst